Enhanced polarization by the coherent heterophase interface between polar and non-polar phases. Issue 14 (25th November 2015) - Kim, Gi-Yeop; Sung, Kil-Dong; Rhyim, Youngmok; Yoon, Seog-Young; Kim, Min-Soo; Jeong, Soon-Jong; Kim, Kwang-Ho; Ryu, Jungho; Kim, Sung-Dae; Choi, Si-Young
Abstract : The electric polarization behavior of a Bi-based piezoelectric ceramic is tuned by building a polar (core)/non-polar (shell) heterostructure. Abstract : A piezoelectric composite containing the ferroelectric polar (Bi(Na0.8 K0.2 )0.5 TiO3 : f-BNKT) and the non-polar (0.94Bi(Na0.75 K0.25 )0.5 TiO3 –0.06BiAlO3 : BNKT–BA) phases exhibits synergetic properties which combine the beneficial aspects of each phase, i.e., the high saturated polarization ( P s ) of the polar phase and the low coercive field ( E c ) of the non-polar phase. To understand the origin of such a fruitful outcome from this type of polar/non-polar heterophase structure, comprehensive studies are conducted, including transmission electron microscopy (TEM) and finite element method (FEM) analyses. The TEM results show that the polar/non-polar composite has a core/shell structure in which the polar phase (core) is surrounded by a non-polar phase (shell). In situ electrical biasing TEM experiments visualize that the ferroelectric domains in the polar core are aligned even under an electric field of ∼1 kV mm −1, which is much lower than its intrinsic coercive field (∼3 kV mm −1 ). From the FEM analyses, we can find that the enhanced polarization of the polar phase is promoted by an additional internal field at the phase boundary which originates from the preferential polarization of the relaxor-like non-polar phase. From the present study, we conclude that the coherent interface between polar and non-polar phases is a key factor for understanding the enhanced piezoelectric properties of the composite.